Level measurement using guided wave radar transducer - Mohd Zain, Zainul Ariffin; Abdul Rahim, Ruzairi; Abdul Rahim, Herlina; Ahmad, Anita (Penerbit UTHM, 2016)
The measurement for level of materials i.e. solid and liquid are widely being used in process control either in any field of industries. For the measuring applications, it can be in mechanical, electrical or even magnetic methods for detecting points which can be continuous or discontinuous for liquid or powder. The point detection is made to trig the level of fillings in the tank or container whether it is high or low. For the level-type transducer, they can be categorized into several classes: • RF capacitance • Conductance (conductivity) • Hydrostatic head/tank gauging • Radar • Ultrasonic • Float • Paddlewheel For the microwave level transducer it is categorized as the radar-type class as both system are literally same but differ in energy levels and their range. Besides, microwave level transducers provides both contact and non-contact method while radar only has non-contact method. Generally, the electromagnetic radiation is energy which is discharged from mobile, electric charges and spreads out as a wave. The wavelength of this radiation decreases with increasing energy. If the wavelength is in the range 1 mm to 1 m (300 MHz to 300 GHz), one refers to microwaves. Household microwave ovens produce radiation with a fixed frequency of 2.45 GHz. In the electromagnetic spectrum microwaves lie between radio waves (1 m to 104 m) and infrared waves (760 nm to 0.5 mm) [1]. The microwave radiation is produced from the phenomenon of electrical discharge. The electromagnetic pulse is sent out, reflected on the filling material and Level Measurement Using Guided Wave Radar Transducer 24 received again. The echo time of the pulse is proportional to the distance from the surface of the medium. The measurement procedure and the accuracy of the measurement are independent of pressure, temperature, vapor, dust, foam, viscosity, conductivity and pH value. Guided Wave Radar (GWR) is categorized in invasive microwave transducer which have contact with the substance that need to me measured compared to the invasive method like Frequency Modulated Continuous Wave (FMCW) which have no contact with the materials. Each of these methods has both advantages and limitations, and in practice, the selection of the most appropriate method for a certain situation is always made by taking into consideration the specific application requirements (the chemical nature of liquid, process conditions, etc.) [2].